18F-FLT PET changes during radio - therapy combined with cetuximab in head and neck squamous cell carcinoma patients - Hoeben, B.A.W.; Troost, E.G.C.; Bussink, J.; van Herpen, C. M. L.; Oyen, W.J.G.; Kaanders, J. H. A. M. (Nuklearmedizin - NuclearMedicine, 2014)
Aim: Early treatment response of head and neck cancer to radiotherapy concomitant with cetuximab was monitored by repetitive PET imaging with the proliferation tracer 18F-FLT. Patients, methods: Five head and neck cancer patients, treated with radiotherapy and concomitant cetuximab following cetuximab induction, received four 18F-FLT PET-CT scans before and during treatment. Changes in SUVpeak, SUVmean and CT- and PET-segmented gross tumour volumes were evaluated, as were correlations with immu- nohistochemical staining for Epidermal Growth Factor Receptor (EGFR) and Ki-67 (proliferation marker) in pre-treatment tumour biopsies. Results:18F-FLT PET measured tumor responses to the induction dose of ce- tuximab varied from 43% SUVpeak decrease to 47% increase. After start of radiotherapy 18F-FLT PET parameters decreased significantly in all patients. No associations were found between PET parameters and EGFR or Ki-67 expression levels. Conclusion: Proliferation of head and neck carcinomas shows a varying response to cetuximab induction, but consistently decreases after addition of radiotherapy.
Keywords: [18F] fluorothymidine PET; head and neck cancer; cetuximab; radiotherapy; early response monitoring